An Outlaw Thanksgiving - McCully, Emily Arnold (New York : Dial Books, 1998)
TX Bluebonnet 2000/2001 Summary: While traveling with her mother cross-country by train in 1896, a young girl unexpectedly shares Thanksgiving dinner with the notorious outlaw Butch Cassidy.